Nab-paclitaxel plus carboplatin or gemcitabine versus gemcitabine plus carboplatin as first-line treatment of patients with triple-negative metastatic breast cancer: results from the tnAcity trial - Yardley, Denise; Coleman, R.; Conte, P.; Cortes, J.; Brufsky, A.; Shtivelband, M.; Young, R.; Bengala, C.; Ali, H.; Eakel, J.; Schneeweiss, Andreas; de la Cruz-Merino, L.; et al. (Annals of oncology, 2018)
Metastatic triple-negative breast cancer (mTNBC) has a poor prognosis and aggressive clinical course. tnAcity evaluated the efficacy and safety of first-line nab-paclitaxel plus carboplatin (nab-P/C), nab-paclitaxel plus gemcitabine (nab-P/G), and gemcitabine plus carboplatin (G/C) in patients with mTNBC. - Patients and methods - Patients with pathologically confirmed mTNBC and no prior chemotherapy for metastatic BC received (1 : 1 : 1) nab-P 125mg/m2 plus C AUC 2, nab-P 125mg/m2 plus G 1000mg/m2, or G 1000mg/m2 plus C AUC 2, all on days 1, 8 q3w. Phase II primary end point: investigator-assessed progression-free survival (PFS); secondary end points included overall response rate (ORR), overall survival (OS), percentage of patients initiating cycle 6 with doublet therapy, and safety. - Results - In total, 191 patients were enrolled (nab-P/C, n=64; nab-P/G, n=61; G/C, n=66). PFS was significantly longer with nab-P/C versus nab-P/G [median, 8.3 versus 5.5months; hazard ratio (HR), 0.59 [95% CI, 0.38-0.92]; P=0.02] or G/C (median, 8.3 versus 6.0months; HR, 0.58 [95% CI, 0.37-0.90]; P=0.02). OS was numerically longer with nab-P/C versus nab-P/G (median, 16.8 versus 12.1months; HR, 0.73 [95% CI, 0.47-1.13]; P=0.16) or G/C (median, 16.8 versus 12.6months; HR, 0.80 [95% CI, 0.52-1.22]; P=0.29). ORR was 73%, 39%, and 44%, respectively. In the nab-P/C, nab-P/G, and G/C groups, 64%, 56%, and 50% of patients initiated cycle 6 with a doublet. Grade ≥3 adverse events were mainly hematologic.